Upacara Melasti dan Simbolisme Dewa Cili: Eksplorasi Spiritualitas dalam Tradisi Hindu di Desa Adat Kutuh, Kuta Selatan, Badung - Farhaeni, Mutria (Jayapangus Press, 2024)
Melasti Dewa Cili is an expression of gratitude to Ida Sanghyang Widi Wasa for having obtained abundant agricultural fruit through rainwater that comes from sea water. The purpose of this study is to study the Melasti ceremony and symbolism of the Chilean gods: Exploration of spirituality in Hindu Kutuh traditional village, South Kuta, Badung. This research uses a qualitative approach with data collection is observations, interviews and documentation, data collected are analyzed descriptively interpretatively. The results of research show that (1) the Chilean word God consists of two words namely God and Chili. The Sanskrit word God is the root of the word div which means light. God means the sacred light Ida Sanghyang Widi Wasa or manifestation of God. In the village of Kutuh, the symbol of the goddess of Sri was made of a padi tied filled with a Bali Hindu wreath called the Cili God. (2) The purpose of the wages is as described above but the worship of the gods of Cili has more meaning than the expression of gratitude because the Lord Almighty the people have obtained abundant harvest/products of agriculture through the rainwater whose source is the sea. (3) The series of wards of the Gods of Cili include: (a) melis, melasti, mekiis which means the wards in Hindu religion that are generally aimed at purifying themselves inherently and internally; (b) nyejer means upholding, the qualities of God that exists in the human being; (c) masinah means light, bold, sure; (d) century war means the life of man visiting the Tri Kona: utpati (birth), sthiti (living), and pralin (death); (e) maprani means paying wages as an expression to the feelings of Gods.